Practical biochemistry - Damodaran K., Geetha (Jaypee, 2016)
The motive behind writing practical biochemistry was to make the practical concepts of biochemistry clar for medical students in an examination-oriented format. In this edition, most of the diagrammatic figures are replaced by real images in qualitative analysis and spotters sections. This will definitely impart a realistic feeling of learning qualitative test.